ROLE OF MEDIA CAMPAIGNS IN SHAPING MENSTRUAL HYGIENE BEHAVIOURS IN ADOLESCENTS - Thakur, Sarima; Suri, Chanchal Sachdeva; Askari, Dr. Nisa; Kochhar, Dr. Harmeet Kaur; Verma , Amit (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The impact of media campaigns on teenage menstrual hygiene habits is examined in this study. Particular emphasis was given to understand the way media exposure, campaign awareness, along with campaigns' perceived efficacy affect menstrual hygiene knowledge & practices. 100 adolescents from Chandigarh, India were inquired for this research. To investigate relationships amongst media exposure, awareness, & menstrual hygiene practices, descriptive & regression analyses were carried out. Improvement in menstrual hygiene practices can be observed with media exposure & awareness of media campaigns.Perceived efficacy of media campaigns in influencing menstrual hygiene habits was significantly predicted by media exposure along with awareness thru media campaign. Its impact on knowledge and perception was also observed. These findings imply that media campaigns can significantly improve teenage menstrual hygiene practices. More media efforts are required, especially in rural areas so as to understand gaps in knowledge level, improvising behaviour. Acknowledging media shaping health behaviours of adolescents is an essential outcome of this research. It also guides public health experts & politicians to frame policy framework that may enhance menstrual hygiene practices.